2020
DOI: 10.1126/sciimmunol.abc6259
|View full text |Cite
|
Sign up to set email alerts
|

Cellular context of IL-33 expression dictates impact on anti-helminth immunity

Abstract: Interleukin-33 (IL-33) is a pleiotropic cytokine that can promote type 2 inflammation but also drives immunoregulation through Foxp3+Treg expansion. How IL-33 is exported from cells to serve this dual role in immunosuppression and inflammation remains unclear. Here, we demonstrate that the biological consequences of IL-33 activity are dictated by its cellular source. Whereas IL-33 derived from epithelial cells stimulates group 2 innate lymphoid cell (ILC2)–driven type 2 immunity and parasite clearance, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 64 publications
2
81
1
Order By: Relevance
“…This body of work supports vaginal epithelial cells to be the key source of IL-33-mediated type 2 immunity in the FGT during co-infection. Recent studies have identified myeloid sources of IL-33 to play roles in downregulating mucosal inflammation (Hung et al, 2020a(Hung et al, , 2020bJackson et al, 2020;Sell et al, 2020). The findings we present here do not currently suggest a role for cells other than epithelial cells as a contributing source of IL-33.…”
Section: Discussioncontrasting
confidence: 73%
“…This body of work supports vaginal epithelial cells to be the key source of IL-33-mediated type 2 immunity in the FGT during co-infection. Recent studies have identified myeloid sources of IL-33 to play roles in downregulating mucosal inflammation (Hung et al, 2020a(Hung et al, , 2020bJackson et al, 2020;Sell et al, 2020). The findings we present here do not currently suggest a role for cells other than epithelial cells as a contributing source of IL-33.…”
Section: Discussioncontrasting
confidence: 73%
“…The specific stimulation of tTregs by rTsPmy indicates the specific regulation of tTregs in the inflamed colon by helminth-derived protein. A recent study reported that Nippostrongylus brasiliensis and Heligmosomoides polygyrus bakeri drove the ST2 + GATA3 + tTreg responses in intestinal mucosa through DC-derived IL-33 that suppressed helminth immunity (Schiering et al, 2014;Hung et al, 2020). During helminth infection, tTregs are believed to produce the initial regulation of Th2 protective immune responses, while pTregs are developed more slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to one of the pathways for IL-1β, IL-33 secretion has been brought into connection with cell death, while for both interleukins, cell death seems not to be a strict requirement for their release (Kouzaki et al, 2011;Chen et al, 2015;Molofsky et al, 2015;Daniels and Brough, 2017;Ryan et al, 2020). As Hung et al (2020) could show in a recent study, in mouse dendritic cells, IL-33 export was facilitated by perforin-2, which forms pores in the plasma membrane, similar to gasdermin D.…”
Section: Secretion Of Interleukin Il-1βmentioning
confidence: 82%
“…in studies on UPS is increasing. Involved in the most central mechanisms of disease such as inflammation and cancer cell proliferation and, specifically for this review, secretion of virulence factors in parasites, it is of crucial importance FGF2, HIV- TAT Temmerman et al, 2008;Zeitler et al, 2015;Legrand et al, 2020 Type II No ABC-transporters, N-terminal domain HASPB, PfAK2 Denny et al, 2000;Stegmayer et al, 2005;MacLean et al, 2012;Thavayogarajah et al, 2015;Kim et al, 2018 Type III No Vesicles, inflammasome, heat shock protein, GRASP, ESCRTs IL-1β, Acb1, HMGB1 Nickel and Rabouille, 2009;Dupont et al, 2011;Curwin et al, 2016;Cruz-Garcia et al, 2020;Kim et al, 2020 Type IV Yes Golgi bypass via pericentrosomal intermediate compartment, transmembrane domain CFTR Rabouille et al, 2012;Gee et al, 2018;Kim et al, 2018 Pore formation No Gasdermin D, perforin-2 IL-1β, IL-33 Martín-Sánchez et al, 2016;Heilig et al, 2017;Lieberman et al, 2019;Hung et al, 2020 IL-1β is highlighted to emphasize its known use of two different UPS pathways. FGF2, fibroblast growth factor 2; HASPB, hydrophilic acylated surface protein B; GRASP, Golgi reassembly stacking protein; PI(4,5)P 2 , phosphatidylinositol-4,5-bisphosphate; CFTR cystic fibrosis transmembrane conductance regulator; PfAK2, Plasmodium falciparum adenylate kinase 2; ESCRT, endosomal sorting complex required for transport.…”
Section: Introductionmentioning
confidence: 99%